Association between lesion location and language function in adult glioma using voxel-based lesion-symptom mapping - Pia Banerjee; Kevin Leu; Robert J. Harris; Timothy F. Cloughesy; Albert Lai; Phioanh L. Nghiemphu; Whitney B. Pope; Susan Y. Bookheimer; Benjamin M. Ellingson (NeuroImage: Clinical, 2015)
Background: Management of language difficulties is an important aspect of clinical care for glioma patients, and accurately identifying the possible language deficits in patients based on lesion location would be beneficial to clinicians. To that end, we examined the relationship between lesion presence and language performance on tests of receptive language and expressive language using a highly specific voxel-based lesion–symptom mapping (VLSM) approach in glioma patients. Methods: 98 adults with primary glioma, who were pre-surgical candidates, were administered seven neurocognitive tests within the domains of receptive language and expressive language. The association between language performance and lesion presence was examined using VLSM. Statistical parametric maps were created for each test, and composite maps for both receptive language and expressive language were created to display the significant voxels common to all tests within these language domains. Results: We identified clusters of voxels with a significant relationship between lesion presence and language performance. All tasks were associated with several white matter pathways. The receptive language tasks were additionally all associated with regions primarily within the lateral temporal lobe and medial temporal lobe. In contrast, the expressive language tasks shared little overlap, despite each task being independently associated with large anatomic areas. Conclusions: Our findings identify the key anatomic structures involved in language functioning in adult glioma patients using an innovative lesion analysis technique and suggest that expressive language abilities may be more task-dependent and distributed than receptive language abilities.